Global microRNA and protein expression in human term placenta - Östling, Hanna; Lodefalk, Maria; Backman, Helena; Kruse, Robert (Frontiers in Medicine, 2022)
Description of the global expression of microRNAs (miRNAs) and proteins in healthy human term placentas may increase our knowledge of molecular biological pathways that are important for normal fetal growth and development in term pregnancy. The aim of this study was to explore the global expression of miRNAs and proteins, and to point out functions of importance in healthy term placentas. Placental samples (n = 19) were identified in a local biobank. All samples were from uncomplicated term pregnancies with vaginal births and healthy, normal weight newborns. Next-generation sequencing and nano-scale liquid chromatographic tandem mass spectrometry were used to analyse miRNA and protein expression, respectively. A total of 895 mature miRNAs and 6,523 proteins were detected in the placentas, of which 123 miRNAs and 346 proteins were highly abundant. The miRNAs were in high degree mapped to chromosomes 19, 14 and X. Analysis of the highly abundant miRNAs and proteins showed several significantly predicted functions in common, including immune and inflammatory response, lipid metabolism and development of the nervous system. The predicted function inflammatory response may reflect normal vaginal delivery, while lipid metabolism and neurodevelopment may be important processes for the term fetus. The data presented in this study, including supplementary information with complete miRNA and protein findings, will enhance the knowledge base for future research in the field of placental function and pathology.